Deciphering adenosine signaling in hepatocellular carcinoma: Pathways, prognostic models, and therapeutic implications - Huihai Yang; Martina Mang Leng Lei; Longfei Xie; Yinuo Shou; Terence Kin Wah Lee (Clinical and Molecular Hepatology, 2025)
Hepatocellular carcinoma (HCC) is a highly lethal cancer due to its aggressive nature and poor prognosis. Adenosine, a key metabolic regulator in the tumor microenvironment (TME), plays a crucial role in cancer progression. In this review, we first described adenosine triphosphate adenosine metabolism in the TME and summarized its effects on tumor growth, immune suppression, angiogenesis, and metastasis in HCC. Given the limited number of clinical studies on adenosine signaling in HCC, we conducted LASSO-Cox analysis using the TCGA-LIHC cohort to develop a prognostic risk model composed of eight adenosine signaling-related genes. This model stratified the patients into low- and high-risk groups, with Kaplan-Meier survival analysis revealing poorer overall survival in the high-risk group. Additionally, differential gene expression analysis between the two groups identified 24 enriched signaling pathways for further investigation. Immune infiltration and single cell RNA-seq analyses revealed a correlation between adenosine and immunosuppressive activity in the TME, with a particularly strong association observed in macrophages, dendritic cells, and monocytes. Finally, we provided an overview of the advancements of antagonists that target adenosine receptors’ progress in both preclinical research and clinical trials. In conclusion, this review aims to deepen our understanding of the biological role of adenosine and highlights emerging therapeutic strategies that may improve treatment outcomes for HCC.